A new species in the lichen genus Caloplaca from the Canary Islands, including a key to all brown-black Caloplaca sensu lato species in Macaronesia - Pérez-Vargas, Israel; González-Montelongo, Cristina; Padrón, Consuelo Hernández; de Paz, Pedro Luis Pérez (Phytotaxa, 2015)
Caloplaca nigrocarpa sp. nov. found on bark of canary willow from the Canary Islands is described as new to science. A description of the species is given together with notes on its chemistry, distribution, ecology and taxonomy. Related lichen taxa are discussed briefly and a key to the Macaronesian species of the genus Caloplaca s.l. with brown-black apothecia is also provided.